Visibility of the phantom array effect at different LED colour temperatures under high-frequency temporal light modulation. (January 2023) - Kang, HR; Kim, JG; Park, SW; Lee, C-S; Pak, H
LEDs are widely used for both general and automotive lighting since their brightness can be easily regulated by controlling their on/off time using methods such as pulse width modulation (PWM). However, lighting control using PWM can cause temporal light artefacts, such as the phantom array effect, which affect human visual perception. In this study, we determined the influence of different colour temperatures on the visibility of the phantom array effect using five LEDs with different spectral distributions (red, green, blue, warm white and cool white) and frequencies of temporal modulation ranging from 1 kHz to 11 kHz. The threshold of the warm white LED was between that of the green and red LEDs, and threshold of the cool white LED was between that of the red and blue LEDs. The experimental results revealed a difference in the threshold frequency of the visibility of the phantom array effect, in accordance with the spectral distribution and the colour temperature of the light source.